Multilayer ceramic substrate and preparation method thereof
By adding specific additives and sintering additives in the preparation process of multi-layer ceramic substrates, the dispersion of alumina is improved, and polyvinyl alcohol is used to improve the mechanical properties, the problems of bending strength and signal transmission performance of ceramic substrates are solved, and higher integration and electrical properties are achieved.
Patent Information
- Application Number
- CN202510238650.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-03
AI Technical Summary
When traditional single-layer ceramic substrates cope with complex circuit design and high-frequency and high-speed signal transmission, there are problems such as limited number of electronic components, signal distortion, delay and excessive loss, and poor dispersion of alumina in ceramic slurry, which limits the increase in bending strength of multi-layer ceramic substrates.
The preparation method of multi-layer ceramic substrate is adopted, by adding a specific proportion of carboxymethylcellulose calcium and calcium 2,5-dihydroxybenzenesulfonate as additives, combining sintering additives and toughening agents, the dispersion of alumina is improved, and the mechanical properties of the ceramic substrate are improved by the addition of polyvinyl alcohol.
It significantly improves the bending strength and fracture toughness of the multi-layer ceramic substrate, enhances its performance in complex circuits and high-frequency signal transmission, and meets the demands of electronic equipment for high integration, excellent electrical performance and good heat dissipation capabilities.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to a multilayer ceramic substrate and a preparation method thereof. Background Art
[0002] In the era of rapid development of modern electronic information technology, electronic equipment is moving towards miniaturization, lightness, high performance and multi-functional integration. This development trend has put forward more stringent requirements on ceramic substrates, the core basic components of electronic equipment.
[0003] Among many electronic devices, such as smartphones, a large number of complex circuit functions need to be integrated, including high-performance processors, advanced radio frequency modules, large-capacity storage units, etc.; electronic equipment in the aerospace field faces extreme working environments and has extremely high requirements for the stability, reliability and heat dissipation performance of the equipment. These application scenarios urgently require ceramic substrates to have higher integration, better electrical performance, good heat dissipation capabilities and reliable mechanical properties.
[0004] Traditional single-layer ceramic substrates have gradually exposed many limitations in response to these demands. For example, the number of electronic components that can be carried by a single-layer ceramic substrate is limited, making it difficult to meet the wiring requirements of complex circuit designs and unable to achieve highly integrated circuit layouts. In terms of signal transmission, single-layer structures are prone to signal distortion, delay, and excessive loss during high-frequency and high-speed signal transmission, which seriously affects the performance improvement of electronic equipment. In order to solve these problems, multi-layer ceramic substrates came into being.
[0005] However, during the preparation process of multilayer ceramic substrates, the dispersibility of alumina in ceramic slurry cannot be well controlled. Therefore, as the number of layers of the multilayer ceramic substrate increases, this unevenness will gradually accumulate, and the problem of poor dispersibility of alumina will become more prominent, limiting the further improvement of the bending strength of the multilayer ceramic substrate. Therefore, it is necessary to improve the dispersibility of alumina in ceramic slurry and improve the bending strength of the ceramic substrate. Summary of the invention
[0006] The present invention provides a multilayer ceramic substrate and a preparation method thereof, which solves the problem of poor bending strength of the ceramic substrate in the related art.
[0007] The technical solution of the present invention is as follows: The present invention provides a multilayer ceramic substrate, comprising the following raw materials in parts by weight: 100 parts of aluminum oxide, 2-3 parts of a toughening agent, 3-6 parts of a sintering aid, 2-3 parts of a dispersant, 4-8 parts of a binder, 0.5-1 part of an auxiliary agent, 4-6 parts of polyvinyl alcohol, and 30-35 parts of a solvent; the auxiliary agent is composed of calcium carboxymethyl cellulose and calcium 2,5-dihydroxybenzenesulfonate.
[0008] As a further technical solution, the mass ratio of calcium carboxymethyl cellulose to calcium 2,5-dihydroxybenzenesulfonate is 1:1-3.
[0009] As a further technical solution, the mass ratio of calcium carboxymethyl cellulose to calcium 2,5-dihydroxybenzenesulfonate is 1:2.
[0010] As a further technical solution, the solvent is water.
[0011] As a further technical solution, the sintering aid includes calcium oxide, beryllium oxide and strontium oxide.
[0012] In the present invention, the sintering aid can not only form a low melting point eutectic or solid solution with other components in the ceramic substrate, but also promote the density of sintering, and can also make oxygen ions migrate more easily, thereby reducing the internal pores and defects of the ceramic and improving the bending strength of the ceramic substrate.
[0013] As a further technical solution, the preparation method of the sintering aid is: adding calcium oxide, beryllium oxide and strontium oxide into water, adding aliphatic polyoxyethylene ether, mixing and drying, to obtain the sintering aid.
[0014] As a further technical solution, the mixing temperature is 30° C. and the mixing time is 1 hour.
[0015] As a further technical solution, the mass ratio of calcium oxide, beryllium oxide and strontium oxide is 1:2:1.
[0016] As a further technical solution, the added amount of the aliphatic polyoxyethylene ether is 3% of the total mass of calcium oxide, beryllium oxide and strontium oxide.
[0017] As a further technical solution, the ratio of the mass of the solvent to the sum of the mass of calcium oxide, beryllium oxide and strontium oxide is 20:1.
[0018] As a further technical solution, the HLB of the aliphatic polyoxyethylene ether is 6-13, can be 6-7, 9-10, 12-13, and is preferably 9-10.
[0019] In the present invention, adding aliphatic polyoxyethylene ether in the preparation process of sintering aid can reduce the surface tension of the solvent, avoid the agglomeration of calcium oxide, beryllium oxide and strontium oxide, make the components of sintering aid evenly distributed, can play a role more fully and evenly in the subsequent sintering, and improve the bending strength of ceramic substrate. Aliphatic polyoxyethylene ethers with different HLB values have different hydrophilic and lipophilic properties. The inventors found that the HLB value of aliphatic polyoxyethylene ethers will affect the bending strength of ceramic substrates. When the HLB value is 9-10, it can better interact with calcium oxide, beryllium oxide and strontium oxide, prevent the agglomeration of the three sintering aids, and have a certain steric stabilization effect. However, when the HLB value of aliphatic polyoxyethylene ether is not in the range of 9-10, the bending strength of the ceramic substrate decreases.
[0020] As a further technical solution, the toughening agent includes cerium oxide, aluminum oxide fiber, and yttrium oxide.
[0021] As a further technical solution, the mass ratio of cerium oxide, aluminum oxide fiber and yttrium oxide is 1:4:1.
[0022] As a further technical solution, the added amount of the organic amine substance is 4% of the total mass of the alumina fiber, cerium oxide and yttrium oxide.
[0023] As a further technical solution, the preparation method of the toughening agent is: adding cerium oxide, aluminum oxide fiber, and yttrium oxide into ethanol, and then adding organic amine substances, mixing and drying to obtain the toughening agent.
[0024] As a further technical solution, the mixing temperature is 30° C. and the mixing time is 1 hour.
[0025] As a further technical solution, the ratio of the mass of the solvent to the mass of cerium oxide, aluminum oxide fiber and yttrium oxide is 20:1.
[0026] Alumina fibers can bridge cracks in the ceramic matrix and improve the fracture toughness of the ceramic matrix. When subjected to external forces, cerium oxide can inhibit the growth of grains during the sintering process, making the grain size of the ceramic matrix smaller and more uniform, thereby improving the fracture toughness of the ceramic substrate. Moreover, when the ceramic substrate is subjected to external forces, cerium oxide will expand in volume, hindering the expansion of cracks and improving the fracture toughness of the ceramic matrix. Yttrium oxide can be dissolved into the lattice of the ceramic matrix, increasing dislocation movement and improving the fracture toughness of the ceramic substrate. The combination of cerium oxide, alumina fibers and yttrium oxide can better improve the fracture toughness of the ceramic substrate. The addition of organic amines can improve the dispersibility of cerium oxide, alumina fibers and yttrium oxide, and the evenly distributed toughening agent can better improve the fracture toughness of the ceramic substrate.
[0027] As a further technical solution, the organic amine substance includes one or more of ethylenediamine, diethylenetriamine, and triethylenetetramine.
[0028] As a further technical solution, the organic amine substance is diethylenetriamine.
[0029] The inventors found in the process of preparing the toughening agent that the selection of diethylenetriamine can further improve the fracture toughness of the ceramic substrate.
[0030] As a further technical solution, the binder includes one or more of polyvinyl alcohol, polyvinyl butyral, and polyacrylate.
[0031] As a further technical solution, the dispersant includes one or more of acrylate, polyvinyl pyrrolidone, and triethyl phosphate.
[0032] The present invention also provides a method for preparing a multilayer ceramic substrate, comprising the following steps: S1. Weigh alumina, plasticizer, sintering aid, dispersant, additive, polyvinyl alcohol, and solvent, and stir to obtain a mixture; S2, adding a binder to the mixture, stirring to obtain a slurry, and casting the slurry to obtain a green porcelain sheet; S3, after punching holes in the green ceramic sheet, surface printing, lamination and pressing, upper and lower conduction, cutting, sintering, and cooling to obtain a multilayer ceramic substrate.
[0033] As a further technical solution, in S3, the sintering is performed at a heating rate of 5-10°C, the temperature is increased to 1400-1450°C, and the temperature is kept at this temperature for 8-10 hours.
[0034] The working principle and beneficial effects of the present invention are: In the present invention, a specific proportion of calcium carboxymethyl cellulose and calcium 2,5-dihydroxybenzenesulfonate are added to the multilayer ceramic substrate on the basis of adding a dispersant, which can better improve the dispersibility of aluminum oxide in the preparation process, improve the density of the material in the molding process, and reduce internal defects; the addition of polyvinyl alcohol can also serve as a plasticizer to improve the mechanical properties of the multilayer ceramic substrate, which helps to improve the bending strength of the multilayer ceramic substrate. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In the following examples and comparative examples: Fatty alcohol polyoxyethylene ether-3, HLB 6~7; fatty alcohol polyoxyethylene ether-4, HLB 9~10; fatty alcohol polyoxyethylene ether-7, HLB 12~13; alumina, average particle size 50nm; calcium oxide, average particle size 44μm; beryllium oxide, average particle size 1μm; strontium oxide, average particle size 1μm; alumina fiber, model 95, manufacturer Shandong Dongheng Guoxian New Materials Co., Ltd.; carboxymethyl cellulose calcium: model 01, manufacturer Shandong Gukang Bioengineering Co., Ltd.
[0037] Example 1 A method for preparing a multilayer ceramic substrate comprises the following steps: S1. Weigh 100 parts of aluminum oxide, 3 parts of sintering aid, 0.5 parts of aid, 2 parts of acrylate, 4 parts of polyvinyl alcohol 200, 2 parts of toughening agent, and 30 parts of water, and stir to obtain a mixture; wherein the sintering aid is obtained by uniformly mixing calcium oxide, beryllium oxide, and strontium oxide in a mass ratio of 1:2:1; the toughening agent is obtained by uniformly mixing cerium oxide, aluminum oxide fiber, and yttrium oxide in a mass ratio of 1:4:1; the aid is composed of calcium carboxymethyl cellulose and calcium 2,5-dihydroxybenzenesulfonate in a mass ratio of 1:1; S2, adding 4 parts of polyvinyl alcohol 2488 to the mixture, stirring to obtain slurry, and casting the slurry to obtain a green porcelain sheet; S3. After punching holes in the raw ceramic sheet, the raw ceramic sheet is subjected to surface printing, lamination and pressing, upper and lower conduction, cutting, and the temperature is increased to 1400°C at a heating rate of 5°C, kept at this temperature for 10 hours, and cooled to obtain a multilayer ceramic substrate (40 layers).
[0038] Example 2 S1. Weigh 100 parts of aluminum oxide, 6 parts of sintering aid, 1 part of aid, 3 parts of acrylate, 6 parts of polyvinyl alcohol 200, 3 parts of toughening agent, and 35 parts of water, and stir to obtain a mixture; wherein the sintering aid is obtained by uniformly mixing calcium oxide, beryllium oxide, and strontium oxide in a mass ratio of 1:2:1, and the toughening agent is obtained by uniformly mixing cerium oxide, aluminum oxide fiber, and yttrium oxide in a mass ratio of 1:4:1; the aid is composed of calcium carboxymethyl cellulose and calcium 2,5-dihydroxybenzenesulfonate in a mass ratio of 1:1; S2, adding 8 parts of polyvinyl alcohol 2488 to the mixture, stirring to obtain slurry, and casting the slurry to obtain a green porcelain sheet; S3. After punching holes in the raw ceramic sheet, the raw ceramic sheet is subjected to surface printing, lamination and pressing, upper and lower conduction, cutting, and the temperature is increased to 1450°C at a heating rate of 10°C, kept at this temperature for 8 hours, and cooled to obtain a multilayer ceramic substrate (40 layers).
[0039] Example 3 Compared with Example 1, the only difference is that the auxiliary agent consists of calcium carboxymethyl cellulose and calcium 2,5-dihydroxybenzenesulfonate in a mass ratio of 1:2.
[0040] Example 4 Compared with Example 1, the only difference is that the auxiliary agent consists of calcium carboxymethyl cellulose and calcium 2,5-dihydroxybenzenesulfonate in a mass ratio of 1:3.
[0041] Example 5 Compared with Example 3, the only difference is the preparation method of the sintering aid. The preparation method of the sintering aid in this embodiment is: add calcium oxide, beryllium oxide and strontium oxide in a mass ratio of 1:2:1 to water, add aliphatic polyoxyethylene ether-3, mix at 30°C for 1 hour and then dry to obtain a sintering aid; wherein the amount of aliphatic polyoxyethylene ether added is 3% of the total mass of calcium oxide, beryllium oxide and strontium oxide; the ratio of the mass of water to the total mass of calcium oxide, beryllium oxide and strontium oxide is 20:1.
[0042] Example 6 Compared with Example 5, the only difference is that aliphatic polyoxyethylene ether-3 is replaced by an equal amount of aliphatic polyoxyethylene ether-4.
[0043] Example 7 Compared with Example 5, the only difference is that aliphatic polyoxyethylene ether-3 is replaced by an equal amount of aliphatic polyoxyethylene ether-7.
[0044] Example 8 Compared with Example 6, the only difference is that the preparation method of the toughening agent is different. The preparation method of the toughening agent in this embodiment is: add cerium oxide, aluminum oxide fiber, and yttrium oxide in a mass ratio of 1:4:1 to ethanol, add ethylenediamine, mix at 30°C for 1 hour and then dry to obtain a toughening agent; wherein the amount of ethylenediamine added is 4% of the total mass of aluminum oxide fiber, cerium oxide and yttrium oxide; the ratio of the mass of ethanol to the total mass of cerium oxide, aluminum oxide fiber and yttrium oxide is 20:1.
[0045] Example 9 Compared with Example 8, the only difference is that ethylenediamine is replaced by an equal amount of diethylenetriamine.
[0046] Example 10 Compared with Example 8, the only difference is that ethylenediamine is replaced by an equal amount of triethylenetetramine.
[0047] Comparative Example 1 Compared with Example 1, no auxiliary agent was added.
[0048] Comparative Example 2 Compared with Example 1, calcium 2,5-dihydroxybenzenesulfonate was replaced with an equal amount of carboxymethylcellulose calcium.
[0049] Comparative Example 3 Compared with Example 1, carboxymethylcellulose calcium was replaced with an equal amount of 2,5-dihydroxybenzenesulfonate calcium.
[0050] Experimental Example 1 According to the sample requirements in GB / T 6569-2006 "Test method for bending strength of fine ceramics" (the sample preparation method is: heating the raw ceramic sheet to 1400°C at a heating rate of 5°C, keeping it warm for 10 hours, and cooling it to obtain the result) and the measurement method, the bending strength of the single-layer ceramic substrates in Examples 1 to 7 and Comparative Examples 1 to 3 was measured. The test method was three-point bending. The measurement results are shown in 1.
[0051] Table 1
[0052] The bending strengths in Examples 1 to 7 of the present invention are all higher than those in Comparative Examples 1 to 3, and the bending strength in Example 6 is as high as 518 MPa, which can better meet the requirements in actual use.
[0053] Experimental Example 2 According to the specimen requirements and test methods of GB / T 23806-2009 “Fine Ceramics Fracture Toughness Test Method Single Edge Precracked Beam (SEPB) Method”, the fracture toughness of the specimens of Examples 6, 8 to 10 (the specimen preparation method is the same as that of Experimental Example 1) was measured, and the test results are shown in Table 2.
[0054] Table 2
[0055] It can be seen from Table 2 that the fracture toughness in Examples 8 to 10 is better than that in Example 6, indicating that adding organic amine substances can improve the fracture toughness of the ceramic substrate.
[0056] Experimental Example 3 According to the dielectric constant determination method in GB / T 5594.4-2015 "Determination methods for properties of structural ceramic materials for electronic components Part 4: Determination method for dielectric constant and dielectric loss tangent", the dielectric constant of the sample (the sample preparation method is the same as that of Experimental Example 1) is determined, and the results are shown in Table 3.
[0057] Table 3
[0058] It can be seen from Table 3 that the dielectric constant of the ceramic substrate in the present invention can meet the requirements of actual use.
[0059] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A multilayer ceramic substrate, characterized in that: The raw materials include the following components in parts by weight: 100 parts of aluminum oxide, 2-3 parts of toughening agent, 3-6 parts of sintering aid, 2-3 parts of dispersant, 4-8 parts of binder, 0.5-1 part of auxiliary agent, 4-6 parts of polyvinyl alcohol, and 30-35 parts of solvent; the auxiliary agent is composed of calcium carboxymethyl cellulose and calcium 2,5-dihydroxybenzene sulfonate in a weight ratio of 1:1-3.
2. A multilayer ceramic substrate according to claim 1, characterized in that: The sintering aids include calcium oxide, beryllium oxide and strontium oxide.
3. A multilayer ceramic substrate according to claim 2, characterized in that: The preparation method of the sintering aid is as follows: calcium oxide, beryllium oxide and strontium oxide are added into water, and then aliphatic polyoxyethylene ether is added, and the mixture is mixed and dried to obtain the sintering aid.
4. A multilayer ceramic substrate according to claim 3, characterized in that: The HLB of the aliphatic polyoxyethylene ether is 6-13.
5. The multilayer ceramic substrate according to claim 1, characterized in that: The toughening agent includes cerium oxide, aluminum oxide fiber and zirconium oxide.
6. The multilayer ceramic substrate according to claim 5, characterized in that: The preparation method of the toughening agent is as follows: cerium oxide, aluminum oxide fiber and yttrium oxide are added into ethanol, and then organic amine substances are added, mixed and dried to obtain the toughening agent.
7. The multilayer ceramic substrate according to claim 6, characterized in that: The organic amine substances include one or more of ethylenediamine, diethylenetriamine and triethylenetetramine.
8. The multilayer ceramic substrate according to claim 1, characterized in that: The binder includes one or more of polyvinyl alcohol, polyvinyl butyral, and polyacrylate.
9. The multilayer ceramic substrate according to claim 1, characterized in that: The dispersant includes one or more of acrylate, polyvinyl pyrrolidone, and triethyl phosphate.
10. The method for preparing a multilayer ceramic substrate according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh alumina, plasticizer, sintering aid, dispersant, additive, polyvinyl alcohol, and solvent, and stir to obtain a mixture; S2, adding a binder to the mixture, stirring to obtain a slurry, and casting the slurry to obtain a green porcelain sheet; S3, after punching holes in the green ceramic sheet, surface printing, lamination and pressing, upper and lower conduction, cutting, sintering, and cooling to obtain a multilayer ceramic substrate.
Citation Information
Patent Citations
Aluminum oxide ceramic sintered body and production method and application thereof
CN110372337A
High dielectric strength 95 alumina ceramic material and preparation method thereof
CN115650708A
Counterweight cementing material applied to counterweight concrete
CN118324467A
High-purity aluminum oxide ceramic substrate and preparation process thereof
CN119462091A
Alumina porous body and method of producing the same
US20100243557A1
Cited By
Zero-shrinkage low-temperature co-fired multilayer ceramic substrate and preparation method thereof
CN120208653A
High-toughness multilayer ceramic substrate and preparation method thereof
CN120698769A
Aluminum oxide multilayer ceramic substrate with high surface smoothness and preparation method thereof
CN120887710A